Penurunan Bakteri Coli pada Air Sungai Martapura Menggunakan Saringan Arang Sekam Padi - Syarifudin A. (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2017)
Abstract: The Decrease in the Number of Coli Bacteria in Water of Martapura River Using The Husk Charcoal Filter. The habits of the people along the Martapura river, defecates into the river, causing the river water polluted by Coli bacteria that be able to cause disease. Water treatment is required to improve the water quality of the Martapura river, one of them is using